THE MOST IMPORTANT ROLE OF MATHEMATICS IN PRIMARY SCHOOL - Fozilov Jakhongir Ibrokhimovich; Xursanova Zilola Mirzaxolmatovna; Abduraxmonova Mohinur Furqatjon qizi (Galaxy International Interdisciplinary Research Journal, 2022)
Today, in this article, I want to provide information about the role of mathematics in primary school.